Reacción de una persona de 25 años ante la pérdida de un familiar debido a la pandemia covid-19 - Campaña Borja, Job Joel (2021)
This clinical case focuses on the study of the reaction of a 25-year-old person to the loss of a family member due to the COVID-19 pandemic, in which a psychotherapeutic intervention plan was developed with a cognitive-behavioral approach. Where it was possible to establish a diagnosis based on the criteria of the ICD-10 (2000) F33.1 Recurrent depressive disorder, current episode moderate. Which will be developed with the help of psychometric tools such as Beck's depression inventory and the complicated grief inventory, where it was identified that the patient is going through the fourth stage of grief, which is depression. Through the approach, it was possible to apply psychotherapy such as cognitive restructuring, cost-benefit analysis and evaluation of evidence in the face of negative automatic thoughts. The results were favorable in which the patient managed to express their feelings through the farewell letter technique, accepted the loss and continued with their daily activities and responsibilities.